Validating the Valencian association Centaureo rouyi-Cistetum albidi. - Pérez Badia, Rosa (Lazaroa, 2014)
The name Cenzaureo rouyi-Cisteuon albidi Costa & Pérez Lilia, invalidly published due to the ommission of the nomenclatural type, is validated here.